Diversity and enzyme production by yeasts isolated from raw milk in Southern Brazil - Spanamberg, Andréia; Hartfelder, Claudia; Fuentefria, Alexandre Meneghello; Valente, Patrícia (Acta Scientiae Veterinariae, 2018)
Raw milk is generally considered an ideal environment for the growth of many microorganisms because of its nutrient richness. Although there have been numerous reports on the occurrence of yeasts in dairy products in the world, few have attempted to determine the diversity of these microorganisms in samples from raw milk, mainly in Brazil. Thirty six samples were collected from 25 dairy farms located at different districts of Rio Grande do Sul, during a period of 5 months. A total of 80 isolates were obtained and identified according to standard methods. Of these, 63 strains corresponded to true yeasts (51 with ascomycetic and 12 with basidiomycetic affinity), and 17 isolates were recognized as yeast-like strains. Yeast distribution was uneven among the producers analyzed. The most frequent yeasts isolated in this study belong to the genera Kluyveromyces, Rhodotorula, Candida, Geotrichum, and Trichosporon. The high frequency of isolation of Geotrichum and Trichosporon from raw milk is of great concern. Almost 79% of our isolates were lipolytic, while only 6% were proteolytic. Although these microorganisms are not expected to survive the pasteurization/sterilization treatments applied during milk processing, their enzymatic activities may alter milk constituents and affect its quality.